2016
DOI: 10.1007/s11356-016-6157-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimized treatment conditions for textile wastewater reuse using photocatalytic processes under UV and visible light sources

Abstract: In this study, photo-Fenton systems using visible light sources with iron and ferrioxalate were tested for the DOC degradation and decolorization of textile wastewater. Textile wastewaters originated after the dyeing stage of dark-colored tissue in the textile industry, and the optimization of treatment processes was studied to produce water suitable for reuse. Dissolved organic carbon, absorbance, turbidity, anionic concentrations, carboxylic acids, and preliminary cost analysis were performed for the propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Analyzer SDI) (ISO 11348-3:2007) on samples withdrawn during UV-C photolysis and the UV-C AOP processes performed in the UV-C reactor, as described previously [47]. Allivibrio fischeri was exposed to samples diluted to different Considering the high ε254nm of LP (12 355 M -1 cm -1 ) at pH 6, its degradation by direct UV-C photolysis could have been supposed.…”
Section: Acute Toxicity Assaysmentioning
confidence: 99%
“…Analyzer SDI) (ISO 11348-3:2007) on samples withdrawn during UV-C photolysis and the UV-C AOP processes performed in the UV-C reactor, as described previously [47]. Allivibrio fischeri was exposed to samples diluted to different Considering the high ε254nm of LP (12 355 M -1 cm -1 ) at pH 6, its degradation by direct UV-C photolysis could have been supposed.…”
Section: Acute Toxicity Assaysmentioning
confidence: 99%
“…As the Fenton process is usually performed in mild conditions and needs simple and lowcost chemicals, it can lead to economically feasible industrial applications. According to the work of Starling et al (2017), the processing cost is estimated somewhere between US$ 0.90 and 2.20 per cubic meter of treated effluent, including the energy costs.…”
Section: H2o2 Photolysis (Equationmentioning
confidence: 99%
“…Countless published studies have demonstrated promising aspects of advanced oxidation processes (AOP) for the degradation of organics pollutants (Fragoso et al, 2009;Guimarães et al, 2012;Vedrenne et al, 2012;Basturk et al, 2015;Abhilasha et al, 2016;Leite et al, 2016;Starling et al, 2017;Manaa et al, 2019;Mittersteiner et al, 2020). In that technique, the organic molecule undergoes successive oxidative breakings through a chain reaction initiated with highly reactive radicals, particularly the hydroxyl (•OH) and hydroperoxyl (•OOH).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Starling et al (2017) visible light sources and iron and ferrioxilates were used to treat organic carbon and color of the textile wastewater (Starling et al, 2017…”
Section: Physico-chemical Processesmentioning
confidence: 99%